2016
DOI: 10.1002/pca.2609
|View full text |Cite
|
Sign up to set email alerts
|

The establishment of efficient bioconversion, extraction, and isolation processes for the production of phyllodulcin, a potential high intensity sweetener, from sweet hydrangea leaves (Hydrangea macrophyllaThunbergii)

Abstract: This promising result would be beneficial to the industrial utilisation of phyllodulcin as a potential high-intensity sweetener.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Phyllodulcin was extracted from hydrangea leaves by following the method reported previously [ 28 ]. Briefly, leaves were harvested in October 2013 (Sugukmiso Co., Daegu, Korea) and freeze-dried until phyllodulcin extraction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phyllodulcin was extracted from hydrangea leaves by following the method reported previously [ 28 ]. Briefly, leaves were harvested in October 2013 (Sugukmiso Co., Daegu, Korea) and freeze-dried until phyllodulcin extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Phyllodulcin was isolated by using a preparative high-performance liquid chromatography system that was equipped with an autosampler and photodiode array (PDA)-UV detector (Thermo-Finnigan Surveyor, Thermo Scientific, Sunnyvale, CA, USA) for purifying phyllodulcin. Final purity and yield of phyllodulcin were 97% and 2.12% (dry basis), respectively [ 28 ]. Purified phyllodulcin was kept in an auto-desiccator (Sanpla Dry Keeper, Sanplatec Corp, Osaka, Japan) until it was used for experiments.…”
Section: Methodsmentioning
confidence: 99%
“…4,5) Natural sources of photoprotective phytochemicals including green tea, coffee, berries, and pomegranate have been reported. 5,6) Hydrangea (Hydrangeaceae) leaves have been consumed as medicine and tea in far-east Asian countries such as Korea, China, and Japan. 7) Some researchers have reported that ex-tracts of hydrangea leaves possess anti-inflammatory, 8) hepatoprotective, 9) and antimalarial activities.…”
Section: Introductionmentioning
confidence: 99%
“…HM is a Hydrangeaceae plant native to the Korean mountains known as “soogook”, and is traditionally used as a folk medicine to treat many diseases such as diabetes and liver disorders. The major components of the HM extract such as phyllodulcin, hydrangenol, and hydrangeic acid has been determined by the high-performance liquid chromatography method [ 19 ]. The biological properties of HM and its active compounds have been reported with respect to antioxidant [ 20 ] anti-diabetic [ 21 ] and anti-malarial [ 22 ] activities.…”
Section: Introductionmentioning
confidence: 99%